Hak Recall Partai Politik Terhadap Status Keanggotaan Dewan Perwakilan Rakyat dalam Sistem Ketatanegaraan Indonesia - Aliksan Rauf, Muhamad Aljebra; Bunga, Marten; Djanggih, Hardianto (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 7 No 4 (2018)DO - 10.24843/JMHU.2018.v07.i04.p03, 2018)
This study aims to analyze the nature of political party recall rights to the membership of the House of Representatives; recall rights of members of the People's Legislative Assembly by political parties whether they are in accordance with the principles of a democratic state based on law; Juridical consequences of recall rights if they remain in the hands of political parties. This type of research is normative law research. The results of the study indicate that the nature of the right of Recall by political parties to the membership of the People's Legislative Assembly is that political party members who sit in parliamentary seats remain supervised by political parties as political organizations that carry on the democratic stage in order to be submissive and obedient to party policies even if they are against the spirit struggle of the people's representatives. The right of a political party's recall is not in accordance with the principles of a democratic state, if the reason for recalling the membership of the House of Representatives is only limited to members of the House of Representatives who violate the Articles of Association and Household Budget. Penelitian ini bertujuan untuk menganalisis Hakikat hak recall partai politik terhadap keanggotaan Dewan Perwakilan Rakyat; hak recall terhadap anggota Dewan Perwakilan Rakyat oleh partai politik apakah telah sesuai dengan prinsip-prinsip negara demokrasi yang berdasarkan hukum; konsekuensi yuridis hak recall apabila tetap berada di tangan partai politik. Tipe penelitian ini adalah penelitian hukum normatf. Hasil penelitian menunjukkan bahwa hakikat Hak Recall oleh partai politik terhadap keanggotaan Dewan Perwakilan Rakyat adalah agar anggota partai politik yang duduk di kursi parlemen tetap diawasi oleh partai politik sebagai organisasi politik yang mengusung dalam pentas demokrasi agar tunduk dan patuh terhadap kebijakan partai sekalipun bertentangan dengan semangat perjuangan wakil rakyat. Hak Recall Partai Politik tidak sesuai dengan prinsip-prinsip negara demokrasi, apabila alasan merecall keanggotaan Dewan Perwakilan Rakyat hanyalah sebatas anggota Dewan Perwakilan Rakyat melakukan pelanggaran terhadap Anggaran Dasar dan Anggaran Rumah Tangga Partai politik.